Introducing Balinese Language and Cultural Identity Through T-Shirts : A Study of Visual Communication - I Gusti Agung Alit Suryawati (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This paper aims to discuss the meaning of the message of T-shirts labeled with Balinese terms that are traded as tourist souvenirs in Bali. As a result of qualitative research, research data were obtained through observation, document review, and interviews with several informants of t-shirt consumers as well as observers of fashion and Balinese arts and culture. The data collected were analyzed by communication theory and semiotic theory. The results of the study show that the fashion or form of the t-shirt is a t-shirt without a kra decorated with Latin writing or a Balinese script with artistic and ideological expression motifs. T-shirts labeled Balinese have become part of the creative industry for tourist souvenirs that continues to grow in line with the dynamics of Bali tourism. From the perspective of visual communication, the message of a Bali tourism souvenir t-shirt has the following meanings: (1) introducing Bali tourist destinations, (2) as an expression of the soul of the wearer; (3) introducing group identity, (4) information on a moment of Balinese tradition, and (5) introducing Balinese language and cultural identity to the public. T-shirt tourism souvenirs that introduce Balinese cultural identity need to be continuously developed.